2015
DOI: 10.5812/jamm.3(2)2015.26977
|View full text |Cite
|
Sign up to set email alerts
|

Detection of blaSPM-1 Metallo-β-Lactamase Gene in Imipenem-Resistant Pseudomonas aeruginosa Strains Isolated From Hospitalized Patients in Isfahan Hospitals

Abstract: Background: Pseudomonas aeruginosa is an opportunistic human pathogen, which causes serious problems especially in people who have immunodeficiency. Recently, metallo-β-lactamase (MBLs) resistance in this bacterium has led to some difficulties in treating bacterial infections. The blaSPM-1 is one of the MBL gene families, which induces resistance to the carbapenem class antibiotics; this gene has not been previously assessed in Iran. Objectives: Detection and quantification of blaSPM-1-metallo-β-lactamase gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…Lucena et al (2014) concluded that MBL producing strains of P. aeuroginosa (clinical isolates) were 49% resistant for ATM, while Abd El-Baky et al (2013) showed that, MBL-producing P. aeurginosa of clinical isolates were 90.3% resistant for ATM. Sedighi et al (2015) showed that MBL-producing strains of P. aeuroginosa isolated from hospitalized patients were 100% resistant against cefepime and this is accordance with the obtained data in this study. Lucena et al (2014) showed that 93 MBL-producing clinical isolates of P. aeuroginosa were 100% resistant to ciprofloxacin and gentamicin.…”
Section: Effect Of Gamma-radiation On Extended Spectrum βLactamases Asupporting
confidence: 92%
“…Lucena et al (2014) concluded that MBL producing strains of P. aeuroginosa (clinical isolates) were 49% resistant for ATM, while Abd El-Baky et al (2013) showed that, MBL-producing P. aeurginosa of clinical isolates were 90.3% resistant for ATM. Sedighi et al (2015) showed that MBL-producing strains of P. aeuroginosa isolated from hospitalized patients were 100% resistant against cefepime and this is accordance with the obtained data in this study. Lucena et al (2014) showed that 93 MBL-producing clinical isolates of P. aeuroginosa were 100% resistant to ciprofloxacin and gentamicin.…”
Section: Effect Of Gamma-radiation On Extended Spectrum βLactamases Asupporting
confidence: 92%
“…The categorization of MDR and XDR in the present study was done as per standard interim protocols as done in earlier studies (46). A. baumannii is considered as MDR-Ab when it exhibits resistance to at least three different classes of antimicrobial agents mainly beta-lactams (third-generation cephalosporins), aminoglycosides, fluoroquinolones and more recently carbapenems (47)(48)(49). In correlation with this, it was not infrequent in the present investigation 71.23% of the isolates showing multidrug resistance to more than three antimicrobial categories.…”
Section: Discussionsupporting
confidence: 51%
“…Unfortunately, the incidence of β-lactamase-producing K. pneumoniae is on the rise 15 . The detection of different β-lactamase genes in resistant bacteria and characterization of their antimicrobial susceptibility profiles could provide important data regarding high risk factors and infection epidemiology [16][17][18] . To date, only a few studies have investigated the types of β-lactamase-producing Enterobacteriaceae and strains possessing integrons present in Iranian hospitals 19,20 .…”
Section: Introductionmentioning
confidence: 99%